Implementation of Integrated Registration System at BBI Using Zoho CRM and ISO 9001:2015 - Marli Trivana Layan; Winsy Christo Deilan Weku; Stephano Caesar Wenston Ngangi; Mahardika Inra Takaendengan (Universitas Teknokrat Indonesia, 2026)
This study aims to improve the registration system at Brilliant Brain Indonesia (BBI) by implementing Zoho CRM, aligned with ISO 9001:2015 Clause 8 requirements. The existing system faced challenges including time-consuming paper-based forms, frequent data entry errors due to manual input, and fragmented data management across two unintegrated systems. Using the Business Process Improvement (BPI) methodology, which includes Organizing for Improvement, Understanding the Process, and Streamlining phases, this research analyzed and optimized the registration workflow. The Wilcoxon signed-rank test was applied to evaluate the statistical significance of improvements before and after system implementation. The customized Zoho CRM platform utilized features such as webforms, workflow automation, automated validation, and real-time analytics. Results showed a significant reduction in registration processing time from an average of 20 minutes 44 seconds to 17 minutes 55 seconds per registration (14% decrease), and a dramatic reduction in data input time from 4 minutes 3 seconds to 4 seconds per record (98% decrease). These improvements enhanced operational efficiency, data accuracy, and compliance with ISO 9001:2015 Clause 8. Although further module development is needed to fully complete documentation processes, this study demonstrates that integrating cloud-based CRM systems with quality management frameworks can substantially improve educational service operations.